Evaluation of Latex Agglutination Test for Rapid Identification of Staphylococcus aureus Isolated from Pyogenic Wound Infections at a Tertiary Care Hospital - Shah, P; Sah, R; Sharma, A; Khanal, B; Bhattarai, NR (Kathmandu University Medical Journal, 2023)
Background Staphylococcus aureus infections are increasingly reported worldwide. It is a major clinical problem and imposes significant morbidity and mortality due to widespread emergence of multidrug resistant pathogens like methicillin resistant Staphylococcus aureus. Thus, rapid and reliable identification of Staphylococcus aureus is essential for timely and effective management of patient. Objective The performance of Latex agglutination test (Staphaurex Plus) was compared to conventional method tube coagulase test which is gold standard too for the identification of Staphylococcus aureus. Method This study was conducted at B.P. Koirala Institute of Health Sciences. Following standard microbiological methods, isolation and identification was done in the Department of Microbiology. MRSA detection was performed following Clinical and Laboratory Standard Institute. All the isolates of Staphylococci were subjected for Latex agglutination test and was performed according to manufacturer’s instructions using Staphaurex Plus kit. Result Out of 377 (methicillin sensitive Staphylococcus aureus – 142; methicillin resistant Staphylococcus aureus - 233; Coagulase Negative Staphylococci –2) isolates of Staphylococci, Latex agglutination test was found to be positive in 138 (97.1%) of methicillin sensitive Staphylococcus aureus (MSSA) and 220 (94.4%) of methicillin resistant Staphylococcus aureus (MRSA). Overall sensitivity, specificity, positive predictive value and negative predictive value of Latex agglutination test was found to be 95.46%, 100%, 100%, 10.52% respectively. Conclusion In conclusion, Latex agglutination test is a rapid and reliable test for the identification of Staphylococcus aureus.